Low cost taper-rig and lpg imprinting (two-in-one) system using a CO2 pulsed laser - Paterno, Aleksander Sade (2013)
A system is proposed to be configured via software and minor optical changes into a taper rig or a long period grating imprinting system. With it, production of assymetric (non-biconical) silica fiber tapers using the stepwise technique[1] has been demonstrated. It is suggested how this technique may be adapted for the POF tapers[2] fabrication. In addition, when imprinting LPGs, the lowest cost was established for the system to be used as a two-in-one machine, containing a minimal set of accessories.